The Effect of Integrative Learning on Improving Understanding of Science Concepts of Grade V Elementary Students Public School 40 Negeri Katon - Firdaus, Riyadh; Herpratiwi; Fitriawan, Helmy; Firdaus, Rangga (Jurnal PAJAR (Pendidikan dan Pengajaran), 2024)
The problem in this study is the low learning outcomes of fifth grade students of SD Negeri 40 Negeri Katon Pesaaran. The purpose of this study was to determine the effect of integrative learning on increasing the understanding of science concepts of Class V Students of Elementary School Negeri 40 Negeri Katon. The research method used in this research is Quasi Experiment can be interpreted as research that is close to experiments or pseudo experiments. This research design uses a "non-equivalent control-group design", then the two groups are both given a pre-test and post-test, but only the experimental group is given treatment in this study taken using Purposive Sampling technique. Data collection techniques using concept understanding tests, observation and documentation with data analysis using simple linear regression tests the results showed that r count 0 with N = 20 for α = 0.05 obtained r table 0.444; so that r count> r table (0>0.444). Then R square = the magnitude of the termination coefficient (carrying capacity) of the independent variable (Integrative Learning model) in predicting the magnitude of the dependent variable (understanding of the science concept of students) of 0. So it can be concluded that there is an effect of Integrative Learning on increasing the understanding of science concepts of Class V Students of State Elementary School 40 Negeri Katon in the 2023/2024 school year.